Associations between embryo grading and congenital malformations in IVF/ICSI pregnancies. Issue 6 (December 2019) - Abel, Kate; Healey, Martin; Finch, Sue; Osianlis, Tiki; Vollenhoven, Beverley
Abstract: Research question: Does the quality of transferred embryos have an impact on the rate of congenital malformations in IVF/intracytoplasmic sperm injection (ICSI)-conceived babies? Design: Retrospective cohort study involving 6637 pregnancies of ≥20 weeks' gestation from women undergoing embryo transfer with a single Day 5 embryo at a private multisite IVF clinic between 2005 and 2015. Embryos were classified as good quality ( n = 5537) or poor quality ( n = 1100) based on an internal grading system of morphological parameters; malformation rates were compared. Results: In pregnancies proceeding to delivery (≥20 weeks' gestation), poor quality embryos were associated with increased odds of at least one anomaly (adjusted odds ratio [OR] 1.33, 95% confidence interval [CI] 1.03–1.71), major anomalies (adjusted OR 1.42, 95% CI 1.05–1.91), musculoskeletal anomalies (adjusted OR 2.09, 95% CI 1.35–3.22), particularly talipes (adjusted OR 2.88, 95% CI 1.33–6.25), and the International Classification of Diseases (ICD) classification 'Other congenital malformations' (adjusted OR 2.34, 95% CI 1.13–4.34). Furthermore, for pregnancies ≥9 weeks' gestation, poor embryos had more than double the odds of chromosomal anomalies than good embryos (adjusted OR 2.33, 95% CI 1.30–4.18, P = 0.005). Conclusions: This is the first study to compare the rates of individual congenital malformations for good and poor quality embryos. It provides insight into potential risks of transferring poor quality embryos. In pregnancies ≥20 weeks' gestation, poor quality Day 5 embryos are associated with major malformations, at least one anomaly, musculoskeletal anomalies, talipes and the ICD classification 'Other congenital malformations'. In pregnancies ≥9 weeks' gestation, poor quality Day 5 embryos are associated with chromosomal anomalies.